This discussion board is a place to discuss our Daily Challenges and the math and science
related to those challenges. Explanations are more than just a solution — they should
explain the steps and thinking strategies that you used to obtain the solution. Comments
should further the discussion of math and science.
When posting on Brilliant:
Use the emojis to react to an explanation, whether you're congratulating a job well done , or just really confused .
Ask specific questions about the challenge or the steps in somebody's explanation. Well-posed questions can add a lot to the discussion, but posting "I don't understand!" doesn't help anyone.
Try to contribute something new to the discussion, whether it is an extension, generalization or other idea related to the challenge.
Stay on topic — we're all here to learn more about math and science, not to hear about your favorite get-rich-quick scheme or current world events.
Markdown
Appears as
*italics* or _italics_
italics
**bold** or __bold__
bold
- bulleted - list
bulleted
list
1. numbered 2. list
numbered
list
Note: you must add a full line of space before and after lists for them to show up correctly
# I indented these lines
# 4 spaces, and now they show
# up as a code block.
print "hello world"
# I indented these lines
# 4 spaces, and now they show
# up as a code block.
print "hello world"
Math
Appears as
Remember to wrap math in \( ... \) or \[ ... \] to ensure proper formatting.
2 \times 3
2×3
2^{34}
234
a_{i-1}
ai−1
\frac{2}{3}
32
\sqrt{2}
2
\sum_{i=1}^3
∑i=13
\sin \theta
sinθ
\boxed{123}
123
Comments
Solving problems like these hinge on a very important property of the gcd of two numbers. If d=gcd(x,y), then there exists a,b∈Z such that
ax+by=d
This is termed as Bezout's identity/lemma. The wiki link provides more details on this identity. In our case, we have N=a+k1x=b+k2y. Hence, we get that k1x−k2y=b−a
From Bezout's lemma, we have that there exists k1,k2∈Z for
k1x−k2y=b−a since gcd(x,y)=1. Pick one such k1∗,k2∗∈Z i.e. we have
k1∗x−k2∗y=b−a All the other solutions are given by
k1=k1∗+ny and k2=k2∗+nx (since gcd(x,y)=1 ), where n∈Z. Hence,
N=a+k1∗x+nxy=b+k2∗y+nxy
Note that the above is true since a+k1∗x=b+k2∗y.
Hence,
N≡(a+k1∗x)(modxy)≡b+k2∗y(modxy)
It looks like the Chinese Remainder Theorem for 2 equations. I guess it is that there exists N≡z(modxy) which is a unique solution under Z/xyZ, for N≡a(modx) and N≡b(mody) simultaneously if not mistaken.
Easy Math Editor
This discussion board is a place to discuss our Daily Challenges and the math and science related to those challenges. Explanations are more than just a solution — they should explain the steps and thinking strategies that you used to obtain the solution. Comments should further the discussion of math and science.
When posting on Brilliant:
*italics*
or_italics_
**bold**
or__bold__
paragraph 1
paragraph 2
[example link](https://brilliant.org)
> This is a quote
\(
...\)
or\[
...\]
to ensure proper formatting.2 \times 3
2^{34}
a_{i-1}
\frac{2}{3}
\sqrt{2}
\sum_{i=1}^3
\sin \theta
\boxed{123}
Comments
Solving problems like these hinge on a very important property of the gcd of two numbers. If d=gcd(x,y), then there exists a,b∈Z such that ax+by=d This is termed as Bezout's identity/lemma. The wiki link provides more details on this identity. In our case, we have N=a+k1x=b+k2y. Hence, we get that k1x−k2y=b−a From Bezout's lemma, we have that there exists k1,k2∈Z for k1x−k2y=b−a since gcd(x,y)=1. Pick one such k1∗,k2∗∈Z i.e. we have k1∗x−k2∗y=b−a All the other solutions are given by k1=k1∗+ny and k2=k2∗+nx (since gcd(x,y)=1 ), where n∈Z. Hence, N=a+k1∗x+nxy=b+k2∗y+nxy Note that the above is true since a+k1∗x=b+k2∗y. Hence, N≡(a+k1∗x)(modxy)≡b+k2∗y(modxy)
Log in to reply
Much better.
It looks like the Chinese Remainder Theorem for 2 equations. I guess it is that there exists N≡z(modxy) which is a unique solution under Z/xyZ, for N≡a(modx) and N≡b(mody) simultaneously if not mistaken.